2010
DOI: 10.1016/j.appet.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Restrained eating and memory specificity

Abstract: (Chris Ball) not for publication 1-757-221 1760 (office); 1-757-221 3896 (fax)Restrained Eating and 2 AbstractAutobiographical memories are personal experiences that we store across our life-span. A reduced ability to retrieve specific autobiographical experiences has been reported for a number of clinical populations. Previous research has found that the size of the memory specificity effect can predict disorder occurrence, severity, and treatment success. The current research examined whether a similar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
2
11
2
Order By: Relevance
“…Maladaptive emotion regulation strategies such as emotion avoidance and rumination are proposed to contribute to the maintenance of AN (Racine & Wildes, 2014;Rawal, Park, & Williams, 2010). Therefore, AMT parameters might be important for diagnosis, therapy evaluation and prognosis (Ball, Singer, Kemps, & Tiggemann, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Maladaptive emotion regulation strategies such as emotion avoidance and rumination are proposed to contribute to the maintenance of AN (Racine & Wildes, 2014;Rawal, Park, & Williams, 2010). Therefore, AMT parameters might be important for diagnosis, therapy evaluation and prognosis (Ball, Singer, Kemps, & Tiggemann, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Autobiographical memory (AM) is the storage of all the memories related to personal experiences that contribute to shape one's life (Ball, Singer, Kemps & Tiggeman, 2010). It is the place where cognition, personality and the individual's cognitive functions, parts of the self, narrative abilities and affect regulation meet (Conway & Rubin, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a power 1 We did not assess Body Mass Index (BMI) as we were looking at eating concerns in a healthy cohort. Furthermore, previous work has shown no relationship between BMI and autobiographical memory in clinical and subclinical samples with disordered eating (Ball et al, 2010;Bomba et al, 2014;Laberg and Andersson, 2004). Similarly, Roberts et al (2010) reported no relationship between BMI and set-shifting performance in patients with EDs, as did Giel et al (2012).…”
Section: Participantsmentioning
confidence: 77%